EFEKTIVITAS PENERAPAN MODEL TGT (TEAMS GAMES TOURNAMENTS) BERBANTUAN GAME ULAR TANGGA TERHADAP KEMAMPUAN MENULIS TEKS EKSPLANASI SISWA KELAS IX UPT SPF SMP NEGERI 1 PERCUT SEI TUAN - Renita, Renita Oktavia Gultom; Abdurahman Adisaputera (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effectiveness of the application of the TGT model assisted by the snake and ladder game on the ability to write explanatory texts of class IX students of UPT SPF SMP Negeri 1 Percut Sei Tuan. The study population was 351 students with samples taken randomly, namely the experimental class IX-9 totaling 34 students and the control class IX-11 totaling 30 students. This study used an experimental method with a two-group post-test design, where the test was only conducted once after the treatment was given. The results showed that the ability to write explanatory texts of students in the experimental class using the TGT model assisted by the snake and ladder game obtained an average score of 81.09 included in the good category. Meanwhile, the control class using the direct learning model obtained an average score of 67.13 included in the sufficient category. Based on the results of the hypothesis test using the t test, the t count value was 5.39. This value was then compared with the t table at a significance level of 5% with degrees of freedom (df) 62, which was 2.00. Because the calculated t value is greater than the t table (5.39 > 2.00), the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. Thus, it can be concluded that the TGT model assisted by the snakes and ladders game is more effective than the direct learning model in improving the ability to write explanatory texts.